Autoimmune polyglandular syndrome type I. Features of clinical manifestations, difficulties in diagnosis and methods of correction - G. A. Galkina; L. S. Mikhailichenko; D. I. Sozaeva; S. B. Berezhanskaya; A. A. Afonin (Медицинский вестник Юга России, 2021)
Autoimmune polyglandular syndrome (APG) type I is an orphan disease with autosomal recessive inheritance caused by mutations in the autoimmune regulator gene (AIRE); the disease onset typically occurs in childhood. The disease is characterized by a wide variety of clinical manifestations with a certain stage in the manifestation of individual symptoms. The rare occurrence of this pathology determines its late diagnosis, which can lead to the decompensated life-threatening conditions and an unfavorable outcome. Widely informing pediatric specialists will contribute to the development of a diagnostic algorithm for timely verifying the disease from the moment its first clinical manifestations appear, and will improve the quality and life expectancy of the patients.